2019
DOI: 10.1177/1533033819840000
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in Giant Cell Tumor of Bone: A Review of the Literature

Abstract: Background: Primary and recurrent giant cell tumor of bone is typically benign; however, rarely giant cell tumor of bone can undergo malignant transformation. Malignancy in giant cell tumor of bone may be primary (adjacent to benign giant cell tumor of bone at first diagnosis) or secondary (at the site of previously treated giant cell tumor of bone). Malignant giant cell tumor of bone has a poor prognosis; it is important to distinguish malignant from benign lesions to facilitate appropriate management. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 46 publications
2
136
0
2
Order By: Relevance
“…Several cases of sarcomatous transformation in recurrent GCTB have been described, for example in the tibia with transformation into a high-grade pleomorphic sarcoma after 13 months on denosumab treatment [52] and transformation into a high-grade osteosarcoma in the ischium after 6 months on treatment [53]. Transformation into different types of sarcoma has been described, including undifferentiated pleomorphic sarcoma, fibrosarcoma and osteosarcoma [12,54].…”
Section: Malignant or Sarcomatous Transformation During Denosumab Trementioning
confidence: 99%
“…Several cases of sarcomatous transformation in recurrent GCTB have been described, for example in the tibia with transformation into a high-grade pleomorphic sarcoma after 13 months on denosumab treatment [52] and transformation into a high-grade osteosarcoma in the ischium after 6 months on treatment [53]. Transformation into different types of sarcoma has been described, including undifferentiated pleomorphic sarcoma, fibrosarcoma and osteosarcoma [12,54].…”
Section: Malignant or Sarcomatous Transformation During Denosumab Trementioning
confidence: 99%
“…Some tumours showed aggressive features, such as cortical and subchondral involvement, reactive bony zone in ltration, and soft tissue masses [6,7]. Recently, a study including four large series identi ed 92 cases of malignant GCTB in 2,315 patients; the incidence ranged from 1.1-11.3%, and the cumulative incidence was 4.0% [8]. It is important to perform survival prediction to determine individual treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Some tumors showed aggressive features such as cortical and subchondral involvement, reactive bony zone infiltration, and soft tissue mass [6,7]. Recently, a study including four large series identified 92 cases with malignant GCTB in 2,315 patients, the incidence was from 1.1% to 11.3% and the cumulative incidence was 4.0% [8]. It's important to perform survival prediction for the arrangement of individual treatment.…”
Section: Introductionmentioning
confidence: 99%